Extended-Spectrum β-Lactamases (ESBL) Producing Bacteria in Animals - Chien-Hao Tseng; Chia-Wei Liu; Po-Yu Liu (MDPI AG, 2023)
Animals have been identified as potential reservoirs and vectors of resistance genes, with studies showing that Gram-negative bacteria can acquire resistance through the horizontal transmission of resistance genes on plasmids. It is important to understand the distribution of antimicrobial-resistant bacteria and their drug-resistant genes in animals. Previous review articles mostly focused on a single bacterium or a single animal. Our objective is to compile all ESBL-producing bacteria isolated from various animals in recent years and provide a comprehensive viewpoint. Using a thorough PubMed literature search spanning from 1 January 2020 to 30 June 2022, studies exploring extended-spectrum beta-lactamase (ESBL) producing bacteria in animals were included. ESBL-producing bacteria are present in animals from various countries around the world. The most common sources of these bacteria were farm animals, and the most frequently isolated bacteria were Escherichia coli and Klebsiella pneumoniae. The most detected ESBL genes were blaTEM, blaSHV, and blaCTX-M. The presence of ESBL-producing bacteria in animals highlights the importance of the One Health approach to address the issue of antibiotic resistance. Further research is needed to better understand the epidemiology and mechanisms of the spread of ESBL-producing bacteria in animal populations and their potential impact on human and animal health.